Obtained of powder coatings by detonation spraying - Buitkenov, D; Rakhadilov, B. K.; Sagdoldina, Zh. B.; Maulet, M. (Eurasian Journal of Physics and Functional Materials, 2026)
In this work, consider the aspects of obtaining powder coatings that possessing certain working properties obtained by detonation spraying. Experimental research were carried on the effect of technological parameters of the detonation spraying process on the phase composition and properties of Ti-Si-C coatings. It is determined that when the volume of filling the detonation barrel with an explosive mixture increases to 70% in the detonation wave flow, the Ti3SiC2 powder partially decomposes into TiC consequently the high-speed shock interaction of heated to high temperatures. Installed that when filling the barrel with an explosive mixture of 50% and 60%, a low extent of decomposition of Ti3SiC2 powder can be achieved. It is determined that an increase in the volume content of the TiC phase in the composition of coatings bring to a decrease in the hardness of the Ti-C-Si coating.Recommended CitationBuitkenov, D. B.; Rakhadilov, B. K.; Sagdoldina, Zh. B.; and Maulet, M. (2020) "Obtained of powder coatings by detonation spraying," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 3, Article 6.DOI: https://doi.org/10.29317/ejpfm.2020040306